Student's ability to the argumentation as the basic condition to develop proof conception - Balčiūnas, Sigitas (Lietuvos matematikos rinkinys, 2001)
Empirical investigation is presented in the article. Methods of mathematical truths substantiation, aplied by pupils, are foundout and classified on the basis of mathematical truths argumentation analysis, known by the pupils. Investigation data is used to describe theoretical possibilities, basing upon the pupils' argumentation, to develop proof conception and ability to demonstrate.